1997
DOI: 10.1177/027112149701700405
|View full text |Cite
|
Sign up to set email alerts
|

Family and Professional Perspectives on Early Intervention

Abstract: This study presents findings from a series of focus groups conducted to explore parent and professional experiences and perspectives regarding inclusion and early intervention. The 45 focus group participants consisted of 13 parents of young children (birth through 5 years) with disabilities and 32 professionals representing service providers and administrators from an array of human services programs and agencies such as child care, early intervention, social services, public health, mental health, and public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 24 publications
2
31
0
1
Order By: Relevance
“…Conceptual models of family-professional partnerships have been developed (e.g., Dinnebeil, Hale, & Rule, 1999;Dunst, Trivette, & Johanson, 1994;Wesley, Buysse, & Tyndall, 1997). These models usually distinguish interpersonal (i.e., characteristics of relationships between individuals that enhance or inhibit partnership) and structural (i.e., components of the relationship between agencies or systems that smooth the progress or restrain partnerships) .…”
Section: Family-professional Partnershipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conceptual models of family-professional partnerships have been developed (e.g., Dinnebeil, Hale, & Rule, 1999;Dunst, Trivette, & Johanson, 1994;Wesley, Buysse, & Tyndall, 1997). These models usually distinguish interpersonal (i.e., characteristics of relationships between individuals that enhance or inhibit partnership) and structural (i.e., components of the relationship between agencies or systems that smooth the progress or restrain partnerships) .…”
Section: Family-professional Partnershipsmentioning
confidence: 99%
“…These models usually distinguish interpersonal (i.e., characteristics of relationships between individuals that enhance or inhibit partnership) and structural (i.e., components of the relationship between agencies or systems that smooth the progress or restrain partnerships) . Examples of interpersonal factors include integrity in relationships (i.e., trust and mutual respect) (Dinnebeil et al, 1999), and examples of structural factors include caseload size and resources (Wesley et al, 1997). Again, what is not known is whether the quality of partnerships has an impact on family quality of life or upon satisfaction with services.…”
Section: Family-professional Partnershipsmentioning
confidence: 99%
“…For example, they may experience difficulties in securing access to appropriate services (Warfield & Hauser-Cram, 1996), financial resources to pay for them, and information to analyze program quality (McWilliam et al, 1995;Peck, Carlson, & Helmsetter, 1992;Wesley, Buysse, & Tyndall, 1997). Parents of children with disabilities frequently worry about the attitudes of providers and other children and parents toward their child, large child-staff ratios and class sizes, and inadequate training for child care providers or inadequate time for the individualized instruction their children need (Bailey & Winton, 1987;Guralnick, 1994;Rafferty & Griffin, 2005).…”
Section: Family Choice and Child Care Satisfactionmentioning
confidence: 99%
“…As purported by early childhood special education (Bailey, 2001;Bruder, 2000b;Dinnebeil et al 1999;Mahoney and Filer, 1996;Wesley et al 1997) and disability studies scholars Valle and Aponte, 2002), this study suggested that the early intervention procedures for the families were very much policy driven. The officials usually ensured that all the requirements were completed and the meeting procedures were properly executed.…”
Section: Discussion and Evaluationmentioning
confidence: 64%
“…Studies in the past mostly claimed that parents were more bounded by policy in determining the types of services or available resources (Mahoney and Filer, 1996;McWilliam et al, 1995;Wesley et al 1997). These studies contended that resource availability determined by the state and local legislation steered the scope of families' services in the process.…”
Section: Discussion and Evaluationmentioning
confidence: 99%